PECULIARITIES OF THE FUNCTIONAL MOBILITY OF NEUROMUSCULAR PROCESSES AND ACADEMIC SUCCESS OF MEDICAL STUDENTS IN CONDITIONS OF INFORMATIONAL STRESS - Волинець, Людмила; Овдій, Марія; Пустолякова, Лариса (SWorldJournal, 2025)
The article deals with research of a motor analyzer for the purpose of diagnosing states of long-term or short-term physical and psychological overstrain in medical students. Conducted studies of the Taping test in students allowed to establish their psy